1988
DOI: 10.1002/jnr.490190209
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and kainate effects on the noradrenergic neurons innervating the rat vas deferens

Abstract: The effects of glutamate on the noradrenergic innervation of the rat vas deferens have been investigated. Administration of a single dose of kainate (50 micrograms) to the peripheral noradrenergic ganglia innervating the vas deferens induced a time-dependent decrease of norepinephrine in the organ; after 10 days the norepinephrine concentration had fallen to 35% of control values. This effect was accompanied by a 70% decrease in the potassium-induced release of recently incorporated 3H-norepinephrine. Concomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In fact, application of kainate to peripheral noradrenergic ganglia innervating the rat vas deferens was earlier shown to induce a time-dependent decrease of noradrenaline in this organ (Lara and Bastos-Ramos 1988). Moreover, NMDA receptor activation in isolated segments of the guinea pig colon potentiates the electrically stimulated noradrenaline overflow, a presynaptic effect probably exerted at sympathetic nerve terminals (Cosentino et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, application of kainate to peripheral noradrenergic ganglia innervating the rat vas deferens was earlier shown to induce a time-dependent decrease of noradrenaline in this organ (Lara and Bastos-Ramos 1988). Moreover, NMDA receptor activation in isolated segments of the guinea pig colon potentiates the electrically stimulated noradrenaline overflow, a presynaptic effect probably exerted at sympathetic nerve terminals (Cosentino et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…High-affinity glutamate binding was demonstrated also in membranes obtained from sym pathetic ganglia. This binding was however displaced by kainate and quisqualate, though not by NMDA [45], Hoffmann et al [46] reported that the dissociative anesthetic ketamine, which besides other effects antago nizes the NMDA receptor complex, improved the neuro logical outcome of incomplete cerebral ischemia in rats by a mechanism related to a decrease in plasma catechol amine activity. These authors suggested that ketamine might produce sympatholytic effects in association with anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In the testis, these receptors have a specific affinity for different structures. There is intense anti-mGluR 2/3 immunolabeling of the head of the mature spermatids, spermatozoa, interstitial cells, myoid cells 102 , seminal vesicles 37 , and vas deferens 625 . This distribution suggests that GluRs may be involved in spermatogenesis, spermatozoa motility, testicular development, and vas deferens control.…”
Section: Reproductive Organsmentioning
confidence: 99%
“…This distribution suggests that GluRs may be involved in spermatogenesis, spermatozoa motility, testicular development, and vas deferens control. In fact, GluRs might be important for the contractile activity of the vas deferens and hence in the control of seminal fluid 625 . In the rat female reproductive system, GluRs also have a unique distribution within areas of the reproductive tract 102 .…”
Section: Reproductive Organsmentioning
confidence: 99%